TAGMEMIK KENNET LEE PIKE DALAM NOVEL LEBIH SENYAP DARI BISIKAN KARYA ANDINA DWIFATMA - Khasanah, Uswatun; Yanuarsih, Sri; Letreng, I wayan (Universitas Tanjungpura, 2024)
Tagmemic is a linguistic theory developed by Kennet Lee Pike and used to analyze language, culture, and meaning. This study aims to analyze, clarify, and describe broadly in the preparation of sentence meanings, understood by using the conceptual tool of tagmeme, which focuses on the ethical and emic aspects of meaning consisting of (1) Perspective is a point of view or a description, (2) Hierarchy began with the simplest arrangement, namely words used to make sentences, (3) Context is the form of language based on its origin, and (4) Units are connecting words between two structures; continuous and contradictory. Meanwhile, to understand the structure of sentences using tagmeme characteristics in the form of (1) Slots, (2) Classes, Roles, and (3) Cohesion. The subject is the novel